Intraoperative Pancreatic Assessment in Pancreaticoduodenectomy The Correlation with Pancreatic Fistula Formation - Mazni, Yarman; Syafiuddin, Ardani F; Putranto, Agi S (The New Ropanasuri Journal of Surgery, 2020)
Background Pancreatic cancer affects 25,000 to 30,000 people in the United States each year and is the fourth or fifth leading cause of cancer-related death in this country. It is generally resected by pancreaticoduodenectomy, with or without preservation of the pylorus and proximal duodenum. Anastomotic leaks, intra-abdominal abscesses, and delayed gastric emptying account for most of the perioperative complications after pancreaticoduodenectomy. Anastomotic leaks of pancreas are resulted pancreatic fistula about 45%. A lot of study that have been done to find risk factors of postoperative pancreatic fistula (POPF) with contradictive results. Method This study was done for 70 patients of pancreaticoduodenectomy procedure. Data was collected from medical record in 2016-2019. The data are pancreatic texture, pancreatic duct diameter, pancreaticojejunal anastomotic technique, use of stent in pancreaticojejunal, and POPF. We analyzed the data bivariat with Spearman. Results There are 41,4% male and 58,6% female, Patient with underweight about 21,4%, normoweight 57,1%, overweight 15,7%, dan obese 5,7%. Patient with Diabetes Melitus (DM) about 11,4% and no DM 88,6%. The mean of blood glucose is 136,03 mg/dl. Patient with no POPF about 21,4% and with POPF 78,6%. The A type POPF about 69,1%, B type 14,5%, and C type 16,4%. Pancreatic duct diameter 78,6% and >3 mm about 21,4%. Soft texture pancreas about 22,9% and hard 77,1%. Use of stent about 21,4% and no stent 78,6%. Pancreaticojejunal anastomotic type of dunking or invaginating about 82,9% and duck to mucosa sebanyak 17,1%. The significant risk factor in univariate analysis is diameter of the pancreatic duct (p=0,007). Conclusion Diameter of the pancreatic duct can be used as a risk factor to predict POPF in pancreaticoduodenectomy procedure.